Функционирование топонимов и этнонимов в речи литовцев Латвии - Квашите, Регина (Slavia Centralis, 2020)
The function of toponyms and ethnonyms in the language of Lithuanians in Latvia The article deals with the research of lexis of Lithuanians in Latvia: attention is paid to two specific layers of vocabulary – toponyms and ethnonyms. During the research of toponyms, it was found out that the spectrum of toponyms was not very wide: the titles of both states dominated and among particular settlements – populated localities and those territorially close to them. Functioning of ethnonyms discloses interesting tendencies manifesting the opposition "nativeoutlandish".